Preparation of thermoresponsive poly(N‐vinylcaprolactam‐co‐2‐methoxyethyl acrylate) nanogels via inverse miniemulsion polymerization. Issue 46 (11th July 2019) - Gao, Feng; Mi, Yifang; Wu, Xinlei; Yao, Jun; Qi, Qi; Cao, Zhihai
ABSTRACT: Stimuli‐responsive polymeric nanogels hold great potential in biological applications. In this work, thermoresponsive polymeric nanogels were conveniently prepared through inverse miniemulsion polymerization of two monomers with a good biocompatibility, N ‐vinylcaprolactam and 2‐methoxyethyl acrylate. A macromolecular crosslinker, poly(ethylene glycol) dimethacrylate (PEGDMA), was used to achieve a better thermoresponsiveness, compared with low‐molecular‐weight crosslinkers. The prepared poly( N ‐vinylcaprolactam‐ co ‐2‐methoxyethyl acrylate) (poly(NVCL‐ co ‐MEA)) nanogels could be well redispersed in aqueous systems, displaying a reversible thermoresponsive transition behavior. The influences of the synthesis parameters including the emulsifier content, PEGDMA content, and monomer composition on the particle properties of poly(NVCL‐ co ‐MEA) nanogels both in inverse emulsions and in aqueous dispersions were systematically investigated. Furthermore, the impacts of the monomer composition and PEGDMA content on the thermoresponsiveness of poly(NVCL‐ co ‐MEA) nanogels were also studied. Promisingly, the introduction of MEA monomeric units to the copolymer chains only slightly reduced the thermoresponsiveness of poly(NVCL‐ co ‐MEA) nanogels. This feature allows to improve the biocompatibility of polymeric nanogels by using MEA as the comonomer without need to compromise the thermoresponsiveness of nanogels. © 2019 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2019, 136, 48237. Abstract :